Chemical, Structural, and Electronic Aspects of Formation and Degradation Behavior on Different Length Scales of Ni‐Rich NCM and Li‐Rich HE‐NCM Cathode Materials in Li‐Ion Batteries. Issue 26 (23rd April 2019) - de Biasi, Lea; Schwarz, Björn; Brezesinski, Torsten; Hartmann, Pascal; Janek, Jürgen; Ehrenberg, Helmut
Abstract: In order to satisfy the energy demands of the electromobility market, both Ni‐rich and Li‐rich layered oxides of NCM type are receiving much attention as high‐energy‐density cathode materials for application in Li‐ion batteries. However, due to different stability issues, their longevity is limited. During formation and continuous cycling, especially the electronic and crystal structure suffers from various changes, eventually leading to fatigue and mechanical degradation. In recent years, comprehensive battery research has been conducted at Karlsruhe Institute of Technology, mainly aiming at better understanding the primary degradation processes occurring in these layered transition metal oxides. The characteristic process of formation and mechanisms of fatigue are fundamentally characterized and the effect of chemical composition on cell chemistry, electrochemistry, and cycling stability is addressed on different length scales by use of state‐of‐the‐art analytical techniques, ranging from "standard" characterization tools to combinations of advanced in situ and operando methods. Here, the results are presented and discussed within a broader scientific context. Abstract : A comprehensive summary of the properties of Ni‐rich NCM and Li‐rich HE‐NCM cathode materials for Li‐ion battery applications is provided, with special emphasis on the research undertaken at Karlsruhe Institute of Technology. Degradation mechanisms on different length scales—including the processes occurring during formation and the fatigue behavior—are reviewed with respect to cell chemistry, electrochemistry, and cycling stability.